A cluster-randomised controlled trial to test the efficacy of facemasks in preventing respiratory viral infection among Hajj pilgrims - Wang, Mandy; Barasheed, Osamah; Rashid, Harunor; Booy, Robert; El Bashir, Haitham; Haworth, Elizabeth; Ridda, Iman; Holmes, Edward C.; Dwyer, Dominic E.; Nguyen-Van-Tam, Jonathan; Memish, Ziad A.; Heron, Leon (Elsevier, 2014)
BACKGROUND: Cost-effective interventions are needed to control the transmission of viral respiratory tract infections (RTIs) in mass gatherings. Facemasks are a promising preventive measure, however, previous studies on the efficacy of facemasks have been inconclusive. This study proposes a large-scale facemask trial during the Hajj pilgrimage in Saudi Arabia and presents this protocol to illustrate its feasibility and to promote both collaboration with other research groups and additional relevant studies.